A Sequence-Specific Nicking Endonuclease from Streptomyces: Purification, Physical and Catalytic Properties. (21st August 2013) - Somyoonsap, Peechapack; Kitpreechavanich, Vichein; Pornbanlualap, Somchai
Abstract : A sequence-specific nicking endonuclease from Streptomyces designated as DC13 was purified to near homogeneity. Starting with 30 grams of wet cells, the enzyme was purified by ammonium sulfate fractionation, DEAE cellulose, and phenyl-Sepharose chromatography. The purified protein had a specific activity 1000 units/mg and migrated on SDS-PAGE gel with an estimated molecular weight of 71 kDa. Determination of subunit composition by gel filtration chromatography indicated that the native enzyme is a monomer. When incubated with different DNA substrates including pBluescript II KS, pUC118, pET-15b, and pET-26b, the enzyme converted these supercoiled plasmids to a mixture of open circular and linear DNA products, with the open circular DNA as the major cleavage product. Analysis of the kinetic of DNA cleavage showed that the enzyme appeared to cleave super-coiled plasmid in two distinct steps: a rapid cleavage of super-coiled plasmid to an open circular DNA followed a much slower step to linear DNA. The DNA cleavage reaction of the enzyme required Mg 2+ as a cofactor. Based on the monomeric nature of the enzyme, the kinetics of DNA cleavage exhibited by the enzyme, and cofactor requirement, it is suggested here that the purified enzyme is a sequence-specific nicking endonuclease that is similar to type IIS restriction endonuclease.